Economic and monetary consequences of Lebanese National debt - Abdul Khalek, Youssef Hussein (Open Science Journal, 2017)
The Lebanese financial condition is miserable. The national debt to GDP is increasing to horrible levels, and the deficits in government is increasing and expected to increase in the subsequent years, the government spending is increasing without any deterrent in the time the revenues to the government are decreasing, the inflation rates are increasing and the economic growth is decreasing. The fallouts of these conditions have direct effect on Lebanese pound and threaten its value. With all the assures from Lebanese central bank governor and the financial officers, a prudent man can sense the risk that is coming on the Lebanese pound and never believe that the Lebanese pound will stay forever the mountain that never lean with wind. Lebanon must take rapid corrective actions to save the country and its currency from a disaster that would howl. Corrective actions of economic, financial, political, and direct reforms must be studied and activate it directly before the zero time comes and remorse will not benefit.